Verb valency in non-native Czech - Hudousková, Andrea (Bohemica Olomucensia, 2023)
The paper presents the results of the analysis of verb valency in non-native Czech on the basis of the learner corpus MERLIN. In order to confirm the hypothesis based on previous studies on valency in non-native Czech, i.e. that non-native speakers overuse prototypical patterns and central meanings of verbs, the use of verbs and their valency frames were examined in 148 texts at CEFR levels A2, B1, and B2. The research based on 3350 occurrences of verbs leads to the conclusion that the number of valency patterns and expressed meanings indeed does not significantly increase with higher level of proficiency.
Keywords: verb valency; Czech for foreigners; learner corpus; CEFR levels